2023
DOI: 10.1021/acs.inorgchem.3c00402
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Photochemical CO2 Reduction to CH4 by a Molecular Iron–Porphyrin Catalyst

Abstract: Iron tetraphenylporphyrin complex modified with four trimethylammonium groups (Fe-p-TMA) is found to be capable of catalyzing the eight-electron eight-proton reduction of CO2 to CH4 photochemically in acetonitrile. In the present work, density functional theory (DFT) calculations have been performed to investigate the reaction mechanism and to rationalize the product selectivity. Our results revealed that the initial catalyst Fe-p-TMA ([Cl–Fe­(III)-LR4]4+, where L = tetraphenylporphyrin ligand with a total cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 132 publications
2
6
0
Order By: Relevance
“…The reaction pathway involves three intermediates of *CO 2 , *COOH, and *CO, among which *CO 2 is found to be a weakly bound adduct without electron transfer from Ni to the CO 2 molecule (Table S3). Throughout the catalysis, *COOH generation represents the most endergonic step, which is in agreement with previous theoretical studies. , Clearly, NiNCP–(N – ) furnishes the most favorable CO 2 RR energetics with the key intermediate *COOH being substantially stabilized (Figure b). On the contrary, NiTPP and NiNCP both exhibit a low stabilization ability for *COOH.…”
Section: Resultssupporting
confidence: 90%
“…The reaction pathway involves three intermediates of *CO 2 , *COOH, and *CO, among which *CO 2 is found to be a weakly bound adduct without electron transfer from Ni to the CO 2 molecule (Table S3). Throughout the catalysis, *COOH generation represents the most endergonic step, which is in agreement with previous theoretical studies. , Clearly, NiNCP–(N – ) furnishes the most favorable CO 2 RR energetics with the key intermediate *COOH being substantially stabilized (Figure b). On the contrary, NiTPP and NiNCP both exhibit a low stabilization ability for *COOH.…”
Section: Resultssupporting
confidence: 90%
“…Although not the focus of this study, a great portion of spin distribution was observed on the porphyrin ligands, as shown in Co–N 2 O 2 –COOH intermediates (Fig S11, ESI†). This indicates the non-innocent role of the porphyrin ligands, which has been suggested by Liao et al 86–89 This observation gives us a hint that modifying the porphyrin ligand could further tune the catalytic ability of the Por-COFs.…”
Section: Resultssupporting
confidence: 62%
“…It is worth noting that these newly designed Por-COFs may yield deep-reduction C1 products (CH 3 OH and CH 4 ), especially when combined with photosensitizers, sacrificial electron donors, or supporting materials. 22,82,87,89–91 These aspects merit further exploration, but we have limited this work to CO 2 -to-CO reduction.…”
Section: Resultsmentioning
confidence: 99%
“…The central Fe atom of the porphyrin ring was well-accepted to be the active site for CO 2 reduction, which was consistent with previous reports. 52,53 The second coordination spheres of polyhydroxy groups offer a high local concentration of protons, which enhanced the photocatalytic efficiencies in terms of both rate constant and catalytic selectivity. To further understand the better catalytic performance of MOF-OH than that of MOF-OCH 3 , the Gibbs free energy diagrams for CO 2 reduction to CO were systematically considered and explored (Fig.…”
Section: Resultsmentioning
confidence: 99%